The integration of Prophetic Sunnah and soft skills in patient care: a contemporary perspective in modern healthcare - Jamaludin, Thandar Soe Sumaiyah; Nurumal, Mohd. Said; Che Abdullah, Che Azunie; Mat Isa, Rif'atunnailah; Che Hasan, Muhammad Kamil; Win, Kyu Kyu; Ariyanto, Heri (IIUM Press, 2025)
Background: The Sunnah of the Prophet Muhammad (?) provides a timeless model of compassionate, ethical, and emotionally intelligent behavior that closely aligns with the soft skills essential in modern patient care. As healthcare increasingly recognizes the value of empathy, communication, respect, and moral integrity, the Prophetic tradition offers an authentic framework for integrating spiritual and ethical dimensions into professional practice. The purpose of this conceptual review is threefold: (1) to clarify how soft skills manifest in healthcare as distinct from other contexts; (2) to map these soft-skill domains onto the ethical-behavioural framework of the Prophetic Sunnah; and (3) to propose a conceptual framework for integrating Prophetic traits and values into healthcare education and practice, particularly within Muslim-majority contexts. Methods: To achieve these aims, a narrative review of literature published between 1999 and 2025 was conducted, drawing from healthcare, psychology, and Islamic literature sources. Relevant classical and contemporary references were synthesised to establish conceptual linkages between soft skills and Prophetic characteristics such as rahmah (compassion), amanah (trust), adab (respect), hikmah (communication), and sabar (patience). Results: The findings highlight how the Prophetic Sunnah complements the healthcare competencies and provides a culturally and spiritually grounded approach to soft-skills development. Embedding these values in healthcare education can strengthen moral resilience, enhance patient-centered care, and reinforce professional identity among Muslim healthcare providers. Conclusion: This review concludes that integrating Prophetic-based soft skills within healthcare training represents not only a moral imperative but also a pathway toward more holistic, compassionate, and ethically coherent healthcare systems